Epidermolysis bullosa hereditaria simplex - Kihiczak, N... I. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Blistering is a common childhood phenomenon. There is a group of heterogeneous, genetic mechanobullous diseases termed epidermolysis bullosa (EB) whose hallmark is blistering due to minor trauma or pressure. Some patients with EB may be limited in common extracurricular activities such as playing tennis or hiking, while others may be asymptomatic with occasional blistering. The level of vesiculation within the skin defines three major subtypes of EB: EB simplex, dystrophic EB and junctional EB. We describe a patient and review the simple type of epidermolysis bullosa (EBS), which has an incidence of approximately 10-30 cases per million. The incidence of EBS ismost probably higher than the stated figure, due to underreporting of mild cases. The severity of EBS depends upon the type of underlying defect.
Keywords: Biopsy; dermatologija; Diagnosis; Epidermolysis bullosa simplex; Infant; kožne bolezni; Pathology; Therapy; zdravljenje